2016
DOI: 10.1016/s2352-3018(16)30037-6
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behaviours, HIV testing, and the proportion of men at risk of transmitting and acquiring HIV in London, UK, 2000–13: a serial cross-sectional study

Abstract: 5Background: HIV incidence among men who have sex with men (MSM) in the UK has remained unchanged 6 over the last decade despite increases in HIV testing and antiretroviral (ARV) coverage. Here we examine 7 trends in sexual behaviours and HIV testing among MSM, and explore risk of transmitting and acquiring 8 HIV. 9Methods: Ten cross-sectional surveys between 2000 and 2013 using self-administered questionnaires and 10 oral HIV antibody testing among MSM in London gay social venues. 11 12 Findings: Of 11,876 MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 26 publications
2
56
0
Order By: Relevance
“…MSM attending GUM clinics are at higher risk of human immunodeficiency virus (HIV) infection and sexually transmitted infection (STI) [11, 12]. Antiretroviral treatment coverage is high (90%) for the 38432 MSM accessing HIV care [13].…”
Section: Methodsmentioning
confidence: 99%
“…MSM attending GUM clinics are at higher risk of human immunodeficiency virus (HIV) infection and sexually transmitted infection (STI) [11, 12]. Antiretroviral treatment coverage is high (90%) for the 38432 MSM accessing HIV care [13].…”
Section: Methodsmentioning
confidence: 99%
“…Findings from cross‐sectional studies of GBM in Glasgow and Edinburgh (2005–2011) show that, despite significant increases in HIV testing in the past 12 months, undiagnosed HIV prevalence remained relatively stable and that nearly half of undiagnosed GBM in 2011 reported testing for HIV within the past 12 months 13 . Similarly, cross‐sectional studies of venue‐recruited GBM in London (2000–2013) showed significant increases in past 12 months HIV testing among men with undiagnosed HIV infection (29% to 67%) 14 . When considered alongside modelling of jurisdiction‐specific HIV epidemics suggesting that most of HIV transmissions among GBM are attributed to undiagnosed acute infections, 6,38 these findings support calls for novel strategies to improve HIV testing accessibility to facilitate high frequency testing 13,23,39,40 .…”
Section: Discussionmentioning
confidence: 99%
“…13 Similarly, cross-sectional studies of venue-recruited GBM in London (2000-2013) showed significant increases in past 12 months HIV testing among men with undiagnosed HIV infection (29% to 67%). 14 When considered alongside modelling of jurisdiction-specific HIV epidemics suggesting that most of HIV transmissions among GBM are attributed to undiagnosed acute infections, 6,38 these findings support calls for novel strategies to improve HIV testing accessibility to facilitate high frequency testing. 13,23,39,40 One such strategy is to make prevention interventions like HIV pre-exposure prophylaxis more accessible to motivate GBM who have high risk condomless sex to come forward for testing.…”
Section: Infectious and Communicable Diseasementioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, national trends show a steadily increasing number of HIV diagnoses in MSM, and evidence from community-based surveys of sexual behaviour in MSM suggest that there is a need to enhance the existing HIV prevention package. Community-based surveys have shown increases in UAI with casual partners,16 17 self-reported STIs16 and UAI with a main partner of a different HIV status 18…”
Section: Discussionmentioning
confidence: 99%